LES PRATIQUES LANGAGIÈRES DES LAISSÉS-POUR-COMPTE DANS L’OLYMPE DES INFORTUNÉS DE YASMINA KHADRA - Meriem Belkaid (Studii de gramatică contrastivă)
The Olympus of Misfortunes by Yasmina Khadra immerses us in the fascinating world of a community of misfits living in a public dump. Rejected by society, these “Horr” forge an alternative existence with their own philosophy. The novel explores their Odyssey and the depths of their exclusion, while focusing on the richness of their languages and the complexity of their identities. The central question is how the speech register of these characters defines their status in society. To answer this, the analysis of the different languages used is necessary, starting with the image that the protagonists have of the city.